Dual protocol performance using WiFi and ZigBee for industrial WLAN - Afifi, Ghada (AUC Knowledge Fountain, 2016)
The purpose of this thesis is to study the performance of a WNCS based on utilizing IEEE 802.15.4 and IEEE 802.11 in meeting industrial requirements as well as the extent of improvement on the network level in terms of latency and interference tolerance when using the two different protocols, namely WiFi and ZigBee, in parallel. The study evaluates the optimum performance of WNCS that utilizes only IEEE 802.15.4 protocol (which ZigBee is based on) without modifications as an alternative that is low cost and low power compared to other wireless technologies. The study also evaluates the optimum performance of WNCS that utilizes only the IEEE 802.11 protocol (WiFi) without modifications as a high bit network. OMNeT++ simulations are used to measure the end-to-end delay and packet loss from the sensors to the controller and from the controller to the actuators. It is demonstrated that the measured delay of the proposed WNCS including all types of transmission, encapsulation, de-capsulation, queuing and propagation, meet real-time control network requirements while guaranteeing correct packet reception with no packet loss. Moreover, it is shown that the demonstrated performance of the proposed WNCS operating redundantly on both networks in parallel is significantly superior to a WNCS operating on either a totally wireless ZigBee or WiFi network individually in terms of measured delay and interference tolerance. This proposed WNCS demonstrates the combined advantages of both the IEEE 802.15.4 protocol (which ZigBee is based on) without modifications being low cost and low power compared to other wireless technologies as well the advantages of the IEEE 802.11 protocol (WiFi) being increased bit rate and higher immunity to interference. All results presented in this study were based on a 95% confidence analysis.